Manajemen E-Government Dalam Rangka Capacity Building Birokrasi Di Indonesia - Chazienul Ulum, (Bisnis dan Manajemen, 2010)
The striving forward efoorts for bureaucracy capacity bulding by increasing performance and institution services corstitute surely. This paper discussing about many issue related to capacity building and bureaucracy innovation forward e-government management in Indonesia. The optinalisatim of suitable implementation e-government can supporting transpiration and public accountabilities. otherwise. The effectiveness of e-government management can reaches if bureaucracy and stakeholders have readiness for using information technology and communication.